2019
DOI: 10.1177/1060028019849716
|View full text |Cite
|
Sign up to set email alerts
|

Intravenous Acetaminophen–Induced Hypotension: A Review of the Current Literature

Abstract: Objective: Recent literature suggests that intravenous (IV) administration may cause hypotension in hospitalized patients; data further suggest that this effect is most pronounced in the critically ill. The purpose of this review is to identify and evaluate current literature that addresses the incidence and implications of IV acetaminophen–induced hypotension. Data Sources: A literature search of MEDLINE, Cochrane, and EMBASE databases was performed (2002-2019) using the following terms: acetaminophen, parace… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 25 publications
(30 citation statements)
references
References 40 publications
0
30
0
Order By: Relevance
“…Without close observation, patients may have a paracetamol‐induced trough in BP, which vastly goes undetected (Figure 2). Despite the evidence described in the literature, there are currently insufficient haemodynamic warnings available within disclosures made by pharmaceutical companies that market paracetamol (Kelly et al., 2016; Maxwell et al., 2019). Counterintuitively, such omission can influence clinical practice guidelines for safe paracetamol administration.…”
Section: Discussionmentioning
confidence: 99%
“…Without close observation, patients may have a paracetamol‐induced trough in BP, which vastly goes undetected (Figure 2). Despite the evidence described in the literature, there are currently insufficient haemodynamic warnings available within disclosures made by pharmaceutical companies that market paracetamol (Kelly et al., 2016; Maxwell et al., 2019). Counterintuitively, such omission can influence clinical practice guidelines for safe paracetamol administration.…”
Section: Discussionmentioning
confidence: 99%
“…Recent guidelines [ 29 ] confirm the nonsignificant difference between IV and oral formulations in terms of pain scores, rescue medication, and AEs, with reduced costs of oral paracetamol. The risk of hepatotoxicity from therapeutic doses of paracetamol is extremely low, while the risk of hypotension is reported, particularly with IV formulations in critically ill patients [ 52 ].…”
Section: Routes Of Administrationmentioning
confidence: 99%
“…A key mechanism for lowering temperature is by initiation of cutaneous vasodilation, [50][51][52] similar to what occurs during defervescence, which facilitates arterial heat dissipation from the skin. This vasodilation can occur to varying degrees in a febrile patient, but studies in both adults [53][54][55] and children 56,57 have shown this often leads to a clinically significant fall in mean arterial pressure. The subsequent acetaminophen-induced hypotension is then countered with fluid and/or vasopressor support to maintain adequate organ perfusion.…”
Section: Fluidmentioning
confidence: 99%
“…The subsequent acetaminophen-induced hypotension is then countered with fluid and/or vasopressor support to maintain adequate organ perfusion. [53][54][55][56][57] Thus, a vicious cycle ensues as we desperately work against the normal physiology of the body to maintain blood pressure, but as total body water stores increase, oxygenation in the lungs then becomes compromised, inducing unnecessary harm. 58 The time for an evidence-based approach to fluid management in the febrile patient is long overdue.…”
Section: Fluidmentioning
confidence: 99%